2019
DOI: 10.3389/fpls.2019.00918
|View full text |Cite
|
Sign up to set email alerts
|

A High-Density Linkage Map of the Forage Grass Eragrostis curvula and Localization of the Diplospory Locus

Abstract: Eragrostis curvula (Schrad.) Nees (weeping lovegrass) is an apomictic species native to Southern Africa that is used as forage grass in semiarid regions of Argentina. Apomixis is a mechanism for clonal propagation through seeds that involves the avoidance of meiosis to generate an unreduced embryo sac (apomeiosis), parthenogenesis, and viable endosperm formation in a fertilization-dependent or -independent manner. Here, we constructed the first saturated linkage map of tetraploid E. curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 105 publications
(133 reference statements)
2
21
0
Order By: Relevance
“…Although an E. curvula genome assembly is available [ 55 ] and we could have used it as a reference genome, for this study we decided to de novo assemble the reads since the sequenced genome belongs to a sexual diploid genotype and the sequences corresponding to the region that determine apomixis might not be present, as was observed by Zappacosta et al [ 54 ] using molecular markers linked to the trait. The assembly quality analysis, performed with Trinity stats, indicated an N50 of 1553 bp, an average contig length of 919.09 bp and a GC content of 46.38%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although an E. curvula genome assembly is available [ 55 ] and we could have used it as a reference genome, for this study we decided to de novo assemble the reads since the sequenced genome belongs to a sexual diploid genotype and the sequences corresponding to the region that determine apomixis might not be present, as was observed by Zappacosta et al [ 54 ] using molecular markers linked to the trait. The assembly quality analysis, performed with Trinity stats, indicated an N50 of 1553 bp, an average contig length of 919.09 bp and a GC content of 46.38%.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, both treatments were conducted with a facultative apomictic cultivar, hence we expected to find mostly apomictic/sexual regulators, not apomictic triggers because they must be present in plants from both treatments. On the other hand, we are working with the knowledge that apomixis in E. curvula is determined by a genomic region [ 54 ] with an epigenetic component modulating the traits [ 40 , 52 ], and apomixis and sexuality co-exist in facultative plants [ 54 ], allowing us to hypothesize that sexuality is being repressed at different levels in apomictic plants. This repression is deregulated by different endogenous [ 56 ] and exogenous stresses [ 40 ], probably mediated by transcriptional and post transcriptional regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct identification of the genes and genomic elements comprised on these apomixis linked loci however has proven difficult. This is because they are commonly recombination-suppressed and flanked by repetitive regions, interfering with sequencing approaches and map-based cloning [10,[35][36][37][38][39][40][41]. In several species studied, apomixis linked loci represent chromosomal regions that largely diverged from corresponding sexual loci.…”
Section: Genetic Loci Linked To Apomixis Typically Represent Hemizygomentioning
confidence: 99%
“…This is due to its particular type of embryo sac development (Eragrostis-type) [ 30 ]. The reproductive mode of this grass was widely studied using different approaches like cyto-embryology [ 31 ], differential gene expression [ 32 , 33 , 34 ], mapping of the apomixis locus [ 35 ], and genome assembly [ 36 ]. Moreover, it was shown that internal and external stressful situations, like water stress, in vitro culture and intraspecific hybridization increase the percentage of sexual embryo sacs in facultative apomictic plants, evidencing the existence of some epigenetic control over the process [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%